The Effects of Residential Mobility on the Education Outcomes of Urban Middle School Students and the Moderating Potential of Civic Engagement. (April 2020) - Voight, Adam; Giraldo-García, Regina; Shinn, Marybeth
Residential mobility is associated with negative education outcomes for urban students, but there is little empirical evidence for school factors that may ameliorate these effects. One such factor may be civic engagement at school. This study analyzed data from 2, 000 urban middle school students to examine the interplay of residential mobility, education outcomes, and school civic engagement. Findings show that students who change residences have lower academic achievement and rates of attendance and that mobile students who are leaders in school groups and attend afterschool programs have more positive education outcomes compared with their mobile peers who are uninvolved.